2019
DOI: 10.1111/modl.12559
|View full text |Cite
|
Sign up to set email alerts
|

L2 Dynamic Assessment: An Activity Theory Perspective

Abstract: Because scaffolded feedback is a key component of dynamic assessment (DA) and is present in some forms of corrective feedback (CF), it can be unclear how the 2 frameworks differ. Further complicating the distinction, many second language (L2) DA studies have focused on how a teacher provides mediation as a series of prompts, usually in reaction to a learner's error, and what that implies for L2 development. To investigate distinctions between DA and CF from an empirical stance rather than solely a theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 58 publications
(80 reference statements)
1
26
0
7
Order By: Relevance
“…Results seem to point in this direction as dynamic glossing outstands traditional glossing and the control group, both in receptive and productive conditions. This is in line with previous research on dynamic instruction and assessment carried out by Poehner (2011), Siekmann andCharles (2013) or Herazo et al (2019). They all observed that providing mediation as a series of prompts helps L2 development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results seem to point in this direction as dynamic glossing outstands traditional glossing and the control group, both in receptive and productive conditions. This is in line with previous research on dynamic instruction and assessment carried out by Poehner (2011), Siekmann andCharles (2013) or Herazo et al (2019). They all observed that providing mediation as a series of prompts helps L2 development.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies carried out by Poehner (2011), Herazo, Davin andSagre (2019), and Rassaei (2020) examine the role of mediated interaction through dynamic techniques. This type of techniques has been used as a type of feedback which is to be distinguished from the traditional corrective feedback.…”
Section: Glosses and Dynamic Techniques In L2 Vocabulary Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of a learner's responses to mediation during DA can provide the mediator with further insights regarding not only what the learner is capable of performing at the moment, but also what they can perform independently in the future (Poehner, ), because according to Vygotsky (), what a learner can do with assistance today, they can perform independently tomorrow. The decrease in the frequency of the prompts and also the explicitness of mediation required by learners to perform a task over time is taken as an indication of development (Herazo et al., ; Poehner, ; Shrestha & Coffin, ). Thus, DA researchers are interested in not only measuring learners' actual scores but also learners' mediated or potential scores (e.g., Poehner & Lantolf, ; Poehner, Zhang, & Lu, ).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of dynamic glosses in the present study has been operationalized based on the sociocultural concept of dynamic assessment (DA) that aims at assessing and at the same time promoting learners' development by presenting learners with appropriate mediation in terms of hints, prompts, leading questions, and so on. In a typical DA session, a teacher or mediator provides graduated assistance or mediation to assess learners' potential and promote development (e.g., Davin, ; Herazo, Davin, & Sagre, ; Lantolf & Poehner, ; Poehner & Lantolf, ). In the same vein, DG is a technique for helping L2 learners identify the correct definition for an unknown L2 word, ultimately promoting vocabulary learning by presenting learners with mediation and graduated assistance instead of providing the learners with the correct definitions at once.…”
mentioning
confidence: 99%